1997
DOI: 10.1086/286049
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Bribing And Policing As Evolutionary Mechanisms For The Suppression Of Within‐Group Selfishness

Abstract: We show that a new, simple, and robust general mechanism for the social suppression of within-group selfishness follows from Hamilton's rule applied in a multilevel selection approach to asymmetrical, two-person groups: If it pays a group member to behave selfishly (i.e., increase its share of the group's reproduction, at the expense of group productivity), then its partner will virtually always be favored to provide a reproductive "bribe" sufficient to remove the incentive for the selfish behavior. The magnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…Concession models predict that skew should positively correlate with relatedness between potential reproductives (Vehrencamp 1983a;Reeve & Ratnieks 1993;Reeve & Keller 1997). In line with this prediction, we found that queen relatedness is higher in the functionally monogynous population than in polygynous populations (Chan & Bourke 1994;Heinze 1995;Hammond et al 2001Hammond et al , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Concession models predict that skew should positively correlate with relatedness between potential reproductives (Vehrencamp 1983a;Reeve & Ratnieks 1993;Reeve & Keller 1997). In line with this prediction, we found that queen relatedness is higher in the functionally monogynous population than in polygynous populations (Chan & Bourke 1994;Heinze 1995;Hammond et al 2001Hammond et al , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…These models start from the premise that aggression is used by dominants to suppress reproduction in subordinates and by subordinates to claim a share of reproduction from dominants. For example, the transactional model of Reeve and Keller (1997) shows that it will always pay a dominant individual to appease a potential challenger by offering it a share of reproduction. By contrast, the tug-of-war model assumes that the distribution of reproduction is the outcome of a scramble competition in which the dominant individual exerts a stronger "tug" (Reeve et al 1998;Cant and Shen 2006).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, concession models set a lower limit on the share of direct reproduction that subordinates will acquire. Even if the dominant has complete control over the allocation of reproduction within the group (as existing concession models in fact assume), it must yield a share at least as great as thè staying incentive' of Reeve & Ratnieks (1993) to avert the threat of subordinate departure (see Reeve & Keller 1997).…”
Section: Discussionmentioning
confidence: 99%